2022
DOI: 10.4103/jos.jos_158_21
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity effect of orthodontic miniscrew-implant in different types of mouthwash

Abstract: CONTEXT: Orthodontic miniscrew implants (OMIs) are widely used as anchorage alternatives, but recent studies revealed the corrosion behavior of OMIs when they come in contact with mouthwashes. The corrosion materials that are released can cause toxicity, allergy, and mutagenicity. AIMS: This study aims to analyze the cytotoxicity effects of OMIs exposed to different types of mouthwash using human gingival fibroblast (HGFs). SETTINGS AND DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Many researchers have noted that surfaces with high corrosion resistance improve cell viability [ 34 , 35 , 36 ]. Significantly, the corrosion resistance of β-phase Ti-alloys is generally believed to exceed those of Ti-alloys with other phase structures (α’, α”, α + β, or β) [ 3 , 37 ], due to elements in β-phase alloys that have high corrosion resistance (such as Zr, Nb, Mo, and Ta) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have noted that surfaces with high corrosion resistance improve cell viability [ 34 , 35 , 36 ]. Significantly, the corrosion resistance of β-phase Ti-alloys is generally believed to exceed those of Ti-alloys with other phase structures (α’, α”, α + β, or β) [ 3 , 37 ], due to elements in β-phase alloys that have high corrosion resistance (such as Zr, Nb, Mo, and Ta) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, different studies have revealed the corrosion behavior of mini-implants when they come into contact with mouthwashes [31]. Any solid material in a chemical environment results in loss of structural integrity, change of structural characteristics, and loss of material substance [32].…”
Section: Maintenance Of Mini-implantsmentioning
confidence: 99%
“…15 Various studies have suggested reducing inflammation rates by taking daily mouthwash safely. 16,17 According to Nugraha et al, they concluded that Robusta Green Coffee Bean (RGCB) ethanol extract might be effective against periimplantitis bacteria in vitro, and chlorogenic acid in RGCB has antibacterial, anti-inflammatory, antioxidant, pro-osteogenic properties, and antibone resorption. 18 According to some researchers, mini-implant failure is interpreted as the occurrence of implant mobility less than 8 months after insertion, causing the implants to be unable to act as an anchor, and implant replacement is required.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Various studies have suggested reducing inflammation rates by taking daily mouthwash safely. 16 17 According to Nugraha et al, they concluded that Robusta Green Coffee Bean (RGCB) ethanol extract might be effective against periimplantitis bacteria in vitro , and chlorogenic acid in RGCB has antibacterial, anti-inflammatory, antioxidant, pro-osteogenic properties, and antibone resorption. 18 …”
Section: Introductionmentioning
confidence: 99%